Contamination of Watersheds, Micro-Watersheds and the Death of Ecological Niches in Huánuco Peru - Paulino, Nicéforo Bustamante; Villegas, Ido Lugo (Journal of Ecohumanism, 2024)
Pollution is a problem of permanent concern to various scholars such as environmentalists, ecologists, educators, anthropologists, historians, geographers, journalists, administrators and researchers of different disciplines, who are all concerned with the preservation, conservation and defence of the environment; nevertheless, there are gaps in specific contexts such as that of the basins and micro-basins and the death of ecological niches in Huánuco. The study objective is addressed to the function of ecological niches in the way of life of the population of the Andean zone of Huánuco - Peru, to answer the questions: What are the main ecological niches with greater influence in the life of the population of the Andean zone of Huánuco - Peru, and how do the ecological niches influence the life of the population of this population? How do the ecological niches influence the economic activity of the region? What are the contaminated ecological niches with repercussions on the population? What is the social behavior of the inhabitants of this Andean zone? The following objectives were formulated to explain the role that ecological niches play in the way of life of the population of the Andean zone of Huánuco - Peru, while the specific objectives were proposed to identify the main ecological niches with greater influence in the life of the population, to determine the influence of the ecological niches on their economic activity, to identify the contaminated ecological niches with repercussions on the population of this region, and to evaluate the social behavior of the inhabitants concerning the ecological niches of their environment. The logical deductive method was used to analyze the studies published, and the inductive method allowed the generalization based on the observations; as a complementary part, the bibliographic file was used, and as materials, the photographic camera, altimeter, cartographic map of Peru, and Earth Google. The study results are the high contamination of the headwaters of the Upper Marañón Basin due to the mining tailings and the irresponsibility of the farmers living on the banks of the Lauricocha and Nupe Rivers. The conclusion is framed by highlighting the importance of ecological niches for living creatures, which have become the habitat of biodiversity, highlighting the flora, fauna and microorganisms in different climates and microclimates found in the riverbeds. These streams, lakes, lagoons, springs and ponds are being polluted, with a severe risk to their continuity in the headwaters of the Marañón River, especially in the headwaters of the Nupe and Lauricocha micro-watersheds.